Author Correction: From taxonomic deflation to newly detected cryptic species: Hidden diversity in a widespread African squeaker catfish - Jirsová, Dagmar; Štefka, Jan; Blažek, Radim; Malala, John O; Lotuliakou, David E; Mahmoud, Zuheir N; Jirků, Miloslav (Scientific reports, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.